PERSEPSI PENGGUNA HONDA VARIO TERHADAP KEHANDALAN SEPEDA MOTOR HONDA VARIO PADA PAGUYUBAN HONDA VARIO JAWA BARAT - Hendriady de Keizer; Gunardi Gunardi; Hani Hatimatunnisani (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
This study aims to examine the perception of Honda Vario users regarding the reliability of their motorcycles within the Paguyuban Honda Vario Jawa Barat community. Reliability is a key factor influencing consumer satisfaction, loyalty, and repurchase decisions. Using a qualitative descriptive approach, data were collected through open-ended questionnaires and semi-structured interviews with 72 community members. The findings reveal that most users have a highly positive perception of Honda Vario's reliability, especially in terms of engine performance, fuel efficiency, riding comfort, ease of maintenance, and spare part availability. These perceptions enhance users' confidence and their willingness to recommend the motorcycle to others. This study emphasizes the importance of consumer feedback in product development and after-sales strategies in the automotive industry. Keywords:User Perception;Product Reliability;Honda Vario;Motorcycle Community; Consumer Loyalty